2009
DOI: 10.1007/s10903-009-9260-9
|View full text |Cite
|
Sign up to set email alerts
|

The Postpartum Depression Screening Scale-Spanish Version: Examining the Psychometric Properties and Prevalence of Risk for Postpartum Depression

Abstract: The Postpartum Depression Screening Scale (PDSS) has been recently used to assess postpartum depression (PPD) in ethnic minority women, including Spanish-speaking Latinas from predominantly Mexico and Puerto Rico. Given the heterogeneity in the countries of origin for Spanish-speaking immigrants to the U.S., this study examined the psychometric properties and prevalence of PPD risk of the Spanish version of the PDSS in a sample of Latina immigrant mothers from predominantly El Salvador and other Central Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 37 publications
8
30
1
1
Order By: Relevance
“…However, immigrants have relatively high postpartum depression prevalence in Western and non-Western countries; this finding may be due to the challenges associated with migration status, racial and cultural differences (Pearlstein et al, 2009;Le et al, 2010;Chien et al, 2012;Hung et al, 2012;Lucero et al, 2012). Women from a low socioeconomic status are also at particularly high risk of postpartum depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, immigrants have relatively high postpartum depression prevalence in Western and non-Western countries; this finding may be due to the challenges associated with migration status, racial and cultural differences (Pearlstein et al, 2009;Le et al, 2010;Chien et al, 2012;Hung et al, 2012;Lucero et al, 2012). Women from a low socioeconomic status are also at particularly high risk of postpartum depression.…”
Section: Discussionmentioning
confidence: 99%
“…The subgroups of populations documented to experience postpartum depression are immigrants, mothers of ill newborn and neonatal intensive care unit infants, epilepsy patients, military wives, women with low socio-economic status, women with preterm birth, and women who experienced a natural disaster. Immigrants have high postpartum depression prevalence of 0.5-65.0% in Western and nonWestern countries (Pearlstein et al, 2009;Le et al, 2010;Chien et al, 2012;Hung et al, 2012;Lucero et al, 2012). Postpartum depression was reported to be 7-70% in mothers of ill newborn (de Alencar et al, 2009;Lefkowitz et al, 2010;Gold et al, 2013;Guo et al, 2013), 13% in mothers of preterm infants (Korja et al, 2008) and 23.5% in mothers of infantile colic infants (Akman et al, 2006).…”
Section: Magnitude Of Postpartum Depressionmentioning
confidence: 99%
“…In other Spanish speaking settings outside Latin America, the PHQ-15 showed a good internal consistency (C-α = 0.78), as did the GDS, when used in visually impaired individuals (C-α = 0.91) and the Postpartum Depression Screening Scale (C-α = 0.97) [20][22]. Adequate internal consistency and discriminative properties were reported for the World Health Organization Disability Assessment Schedule II (WHO-DAS II) (co≥50; ss = 71.4%; sp = 67.6%; proportion of correctly classified individuals (cc) = 70.4%) [22] and for the Euro-D in Spanish elderly (C-α = 0.75; area under the ROC curve auROC = 0.92, co≥3; ss = 91.8%; sp = 76.6%) [23].…”
Section: Introductionmentioning
confidence: 93%
“…Studies have observed rates of PPD in Hispanic women to be considerably higher than women in the majority culture, with estimates ranging from 28–64% (Chaudron et al, 2005; Kuo et al, 2004; Le et al, 2010; Martinez-Schallmoser et al, 2003) as compared to prevalence rates of 7–19% among Caucasian women (Gavin et al, 2005). The incidence of PPD may be similarly elevated among Hispanic men, however research has yet to evaluate prevalence rates within this population.…”
Section: Introductionmentioning
confidence: 99%